THE CHALLENGE OF ABSENTEEISM OF PUBLIC HEALTHCARE CENTERS WORKER IN THE RURAL AREA: A STUDY ON SYLHET DISTRICT, BANGLADESH - Mainul Hasan Niber; Sabbir Amin; Saydur Rahman Nion; Mohammad Rashedur; Rahman Badhan; Muhammad Al Amin (Perkumpulan Dosen Muslim Indonesia, 2024)
Absenteeism has been linked to ineffective healthcare delivery in several studies. This research looks at absenteeism in Bangladesh's public healthcare centers (PHCs), a health system level recognized as vulnerable to absenteeism. Front-line health workers, administrators, service consumers, and health propensity committee chairpersons were interviewed in detail and participated in focus groups. Absenteeism was shown to be quite common among healthcare employees, and it is much more of a problem in PHCs when lateness is included. Absenteeism influences the pair service consumers and associates, although it is not necessarily intentional. Even though there are measures to prevent absenteeism in PHCs, our results reveal that they are readily evaded and ineffectual due to utilization and formative difficulties. The Anti-Corruption Evidence (ACE) strategy, which aims to include and improve the stimulations of significant players in the system to support efficiency-renovating measures and, in turn, ensure efficient service delivery, might be relevant in this case. In this research, we will look at the issues of a lack of health workers in Bangladesh's PHCs, patient satisfaction and the quality of services at PHCs, and the effect of a lack of health workers in Bangladesh's rural public healthcare centers (PHCs).